Travel to high altitude with young children: An approach for clinicians - Yaron, M.; Niermeyer, S. (High Altitude Medicine & Biology, 2008)
As more families travel to mountainous destinations, clinicians are frequently asked for advice regarding children at altitude. We briefly review the principles of altitude illness in children, offer a management plan for the clinician, and highlight the gaps in current evidence. Planning for ascent, altitude illness management, and diagnostic follow-up are discussed.